2005
DOI: 10.1007/s00264-005-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Malignant bone tumors in Kuwait

Abstract: Between 1995 and 2004, 142 malignant bone tumours comprising 76 primary and 66 secondary tumours were identified in the Pathology Department of Al-Sabah Hospital, Kuwait. Pathological fracture was the presenting sign in 35% of the cases. The mean incidence of primary tumours/year was 3.3 cases/million inhabitants. The primary tumours showed a male predilection and 42% occurred below the age of 20 years. The most frequent in the descending order of frequency were Ewing's sarcoma, multiple myeloma, osteosarcoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
(11 reference statements)
3
14
0
Order By: Relevance
“…In addition, unlike the presented study, which found osteosarcoma to be the most common tumour observed, the most common tumour detected was Ewing sarcoma. 20 In India, the annual incidence of Ewing sarcoma was 1.6 per 1,000,000 in males and 1.0 per 1,000,000 in females. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, unlike the presented study, which found osteosarcoma to be the most common tumour observed, the most common tumour detected was Ewing sarcoma. 20 In India, the annual incidence of Ewing sarcoma was 1.6 per 1,000,000 in males and 1.0 per 1,000,000 in females. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Reports from other parts of the world show that the primary bone tumors are relatively uncommon lesions constituting less than 1% of all cancers [1,2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis, proper staging and appropriate treatment are thus necessary to ensure maximum patient survival and maintain optimal function of the affected body parts. Primary bone tumors are relatively uncommon lesions constituting less than 1% of all cancers worldwide [1], [2], [3]. Some of these primary bone tumors display marked intra and international variations in incidence, size and age distribution [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral primitive neuroectodermal tumors (pPNET) are malignant small round-cell tumors that occur predominantly in bones and soft tissue of children and young adults [ 1 ], only in rare cases in other organs and in older patients [ 2 ]. pPNET belong to the Ewing's sarcoma family of tumors and share the same immunohistochemical profiles and molecular genotypes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%